Association between women empowerment and contraceptive utilization in Ethiopia - Yonas Abebe; Robera Demissie Berhanu; Lencho Kajela; Yadeta Babu Bayane (Women's Health)
Background: Women’s empowerment is essential for achieving sustainable development goals. It involves enabling women to take control of their lives by giving them the agency, resources, and opportunities they need to make their own choices and reach their full potential. If more women are empowered to use modern contraceptives, greater reductions in maternal mortality will follow. By understanding this association, we can identify key women empowerment dimensions that have an association with family planning utilization and consider ways forward to improve reproductive health outcomes for women. Objective: This study aimed to investigate the association between women’s empowerment and modern contraceptive utilization among married mothers in Ethiopia. Design: A facility-based quantitative study was employed. Methods: A facility-based quantitative cross-sectional study was employed among 305 mothers selected by systematic random sampling at Jimma Town Public Hospital from July 1 to August 31, 2022. The interviewer-administered questionnaire was used for data collection. The collected data were entered into EpiData Manager, version 4.6.0.6, and then exported to SPSS, version 26. Bivariate and multivariate logistic regression analyses were used to investigate the associations between the dependent and independent variables. Results: Among a total of 305 study subjects, 301 were used in the analysis. Approximately 65% (95% CI = 59.8, 70.8) of the women utilized modern contraceptive methods. High general self-efficacy (AOR = 4.17; 95% CI = 2.11, 8.23), an internal locus of control (AOR = 3.92; 95% CI = 2.01, 7.65), labor work participation (AOR = 4.53; 95% CI = 1.99, 10.31), and enrollment in elementary education (AOR = 8.30; 95%; CI = 2.96, 23.27) have a statistically significant association with modern contraceptive utilization. Conclusion: Numerous dimensions of women’s empowerment are significantly associated with modern contraceptive utilization. The dimension of women’s empowerment needs considerable focus from stakeholders to empower women and enable them to utilize contraceptives and other maternal healthcare services.